Gender Disaggregation in COVID-19 and Increased Male Susceptibility - Acharya, Yogesh; Pant, Suman; Gyanwali, Pradip; Dangal, Ganesh; Karki, Priyanka; Bista, Navindra Raj; Tandan, Meera (Journal of Nepal Health Research Council, 2020)
Novel coronavirus disease 2019 (COVID-19) is a growing public health crisis. Despite initial focus on the elderly population with comorbidities, it seems that large studies from the worst affected countries follow a sex-disaggregation pattern. Analysis of available data showed marked variations in reported cases between males and females among different countries with higher mortality in males.  At this early stage of the pandemic, medical datasets at the individual level are not available; therefore, it is challenging to conclude how different factors have impacted COVID-19 susceptibility. Thus, in the absence of patients’ level data, we attempted to provide a theoretical description of how other determinants have affected COVID-19 susceptibility in males compared to females.  In this article, we have identified and discussed possible biological and behavioral factors that could be responsible for the increased male susceptibility. Biological factors include - an absence of X-chromosomes (a powerhouse for immune-related genes), a high level of testosterone that inhibits antibody production, and the presence of Angiotensin-converting enzyme 2 (ACE2) receptors that facilitate viral replication. Similarly, behavioral factors constitute - higher smoking and alcohol consumptions, low level of handwashing practices, and high-risk behavior like non-adherence to health services and reluctance to follow public health measures in males.Keywords: COVID-19; gender; males; sex disaggregation; susceptibility